2018
DOI: 10.1093/nar/gky568
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 acetylation at lysine 85 regulates chromatin condensation and genome stability upon DNA damage

Abstract: Linker histone H1 has a key role in maintaining higher order chromatin structure and genome stability, but how H1 functions in these processes is elusive. Here, we report that acetylation of lysine 85 (K85) within the H1 globular domain is a critical post-translational modification that regulates chromatin organization. H1K85 is dynamically acetylated by the acetyltransferase PCAF in response to DNA damage, and this effect is counterbalanced by the histone deacetylase HDAC1. Notably, an acetylation-mimic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 63 publications
3
41
0
1
Order By: Relevance
“…Indeed, the GH1 domain contains numerous residues that undergo post-translational modifications (PTMs) (e.g., Wisniewski et al, 2007) that could conceivably modulate GH1-GH1 interactions. In this connection, a recent study investigating the dynamic acetylation of H1 on residue Lys85 (located in the GH1 domain) in response to DNA damage reported that the acetylation mimic mutant H1K85Q dramatically increased the sedimentation rate of reconstituted nucleosome arrays and favored chromatin condensation in cells (Li et al, 2018). It is tempting to speculate that K85 acetylation or Gln substitution induces H1 to adopt a different nucleosome binding mode that favors a more compact fiber conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the GH1 domain contains numerous residues that undergo post-translational modifications (PTMs) (e.g., Wisniewski et al, 2007) that could conceivably modulate GH1-GH1 interactions. In this connection, a recent study investigating the dynamic acetylation of H1 on residue Lys85 (located in the GH1 domain) in response to DNA damage reported that the acetylation mimic mutant H1K85Q dramatically increased the sedimentation rate of reconstituted nucleosome arrays and favored chromatin condensation in cells (Li et al, 2018). It is tempting to speculate that K85 acetylation or Gln substitution induces H1 to adopt a different nucleosome binding mode that favors a more compact fiber conformation.…”
Section: Discussionmentioning
confidence: 99%
“…p53-dependent H3K9 and H3K27 acetylation at sub-telomeric regions prevents γH2AX signal accumulation at telomeres (Tutton et al 2016), suggesting a potential role for histone acetylation in restraining the ATM-dependent DNA damage response in specific chromosomal regions. Recently, we showed that acetylation of linker histone H1, a less-characterized chromatin mark, may also participate in regulating chromatin structure and genome stability in the DNA damage response (Li et al 2018). Together, these studies show that histone acetylation is mainly implicated in ATM activation through altering local or general chromatin structure, and eventually controls a wide aspect of the DNA damage response and DNA repair.…”
Section: Histone Acetylationmentioning
confidence: 92%
“…Although information of site specificity is limited, recent studies using a series of proteomic screening methods have unraveled several sets of ADP-ribosylation targets under stressed conditions and revealed that serine is the major target on histones upon DNA damage (Leidecker et al 2016;Palazzo et al 2018;Fontana et al 2017). Very recently, we identified that PARylation of linker histone H1.2 at serine 188 (S188) mediates H1.2 dynamics and is required for ATM activation upon DNA damage (Li et al 2018) (Fig. 3).…”
Section: Histone Adp-ribosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This recruitment is sustained by the accumulation at the damaged site of DDR RNAs [141]. The general relaxation of the chromatin is achieved through different mechanisms, which include (i) the RNF8/Ubc13/HUWE1 ubiquitylation of Histone H1 [142,143], (ii) the RNF168 mediated K63-ubiquitylation of H2A/B and H2AX [144], and (iii) the PARylation-dependent, proteasomal degradation of H1.2 [145].…”
Section: The Epigenome At Dsbs and During Ddr: Early Epigenetic Eventmentioning
confidence: 99%